Empowering Postpartum Mothers through Postpartum Exercise and Oxytocin Massage (JURNAL PENGMAS KESTRA (JPK), 2025)
Empowering postpartum mothers is an important promotive and preventive strategy to support maternal recovery after childbirth. One of the key indicators of a successful postpartum period is optimal uterine involution. Limited knowledge and skills among postpartum mothers regarding self-care practices, particularly postpartum exercise and oxytocin massage, may increase the risk of postpartum complications such as subinvolution and hemorrhage. Therefore, continuous educational efforts are required to enhance mothers’ abilities to perform appropriate and safe self-care practices independently. This community service activity aimed to empower postpartum mothers by improving their knowledge and skills in performing postpartum exercise and oxytocin massage independently. The activity was conducted at Klinik Pratama Mars, Deli Serdang Regency, in October 2025, using health education, demonstrations, and hands-on practice methods. A total of 28 postpartum mothers participated in this activity. Evaluation was carried out using pre-test and post-test assessments to measure knowledge levels, as well as observation of participants’ practical skills. The pre-test results showed that most postpartum mothers were in the poor (42.8%) and fair (39.3%) knowledge categories. After the intervention, a significant improvement was observed, with 89.3% of participants achieving the good knowledge category and no participants remaining in the poor category. In addition, mothers’ skills in performing postpartum exercise and oxytocin massage also improved, as indicated by an increase in independent practice ability from 21.4% to 82.1%. These findings indicate that an educational and participatory approach is effective in improving postpartum mothers’ knowledge and skills. Empowerment through postpartum exercise and oxytocin massage supports maternal recovery and has strong potential to be sustainably integrated into midwifery services at primary healthcare facilities.